Sensory Property and Benzo(a)Pyrene (Bap) Level in Se’i Processed from Cull Bali Cow Beef (Faculty of Animal Science Universitas Brawijaya, 2020)
The objectives of this experiment were to evaluate the effect of using meat obtained from cull Bali cows differing in body condition score (BCS) on sensory property and benzo(a)pyrene (BaP) level on se’i (Rotenesse smoked beef). A completely randomized design 9x3 was used in this experiment. The nine treatments were BCS 2 with open smoking method (BCS2O), BCS 2 with close smoking method (BCS2C), BCS 2 given liquid smoke (BCS2LS), BCS 3 with open smoking method (BCS3O), BCS 3 with close smoking method (BCS3C), BCS 3 given liquid smoke (BCS3LS), BCS 4 with open smoking method (BCS4O), BCS 4 with close smoking method (BCS4C), and BCS 4 given liquid smoke (BCS4LS). Parameter measured were sensory property and benzo(a)pyrene (bap) content of se’i. The data of sensory property were analyzed using Kruskal-Wallis test followed by Mann-Whitney test. The data of benzo(a)pyrene (BaP) content was analysed using analysis of variance followed by Duncant test. Results showed that se’i produced from group BCS4LS possessed higher score on taste and tenderness, whereas the strongest aroma of se’i was found in se’i processed by both open and close smoking method in all BCS group. The highest benzo(a)pyrene content (0.0052 – 0.0055 ppm) was found in se’i processed by close smoking method in all BCS group, followed by se’i was added liquid smoke in all BCS group. It is suggested that meat of cull Bali cows with BCS4LS could be used to produce se’i with preferable taste,n tenderness and could lower the accumulation of BaP in se’i.